2019
DOI: 10.1097/mcg.0000000000001006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Anti-TNF Therapies For The Prevention of Postoperative Recurrence of Crohn’s Disease

Abstract: On the basis of a NMA combining direct and indirect evidence either adalimumab or infliximab may be used in the postoperative prophylaxis of CD recurrence. There is currently a lack of evidence on the use of other anti-TNF agents in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
1
17
0
3
Order By: Relevance
“…Moreover, patients undergoing anti‐TNF therapy after surgery did not have more AEs than patients who did not undergo surgery 18 . Similar to a previous meta‐analysis, this study showed that anti‐TNF therapy may safely contribute to preventing recurrence and disease development 2–5 . The most important outcomes are the long‐term avoidance of repeated surgery for recurrent lesions and maintaining the patient's quality of life (QOL).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, patients undergoing anti‐TNF therapy after surgery did not have more AEs than patients who did not undergo surgery 18 . Similar to a previous meta‐analysis, this study showed that anti‐TNF therapy may safely contribute to preventing recurrence and disease development 2–5 . The most important outcomes are the long‐term avoidance of repeated surgery for recurrent lesions and maintaining the patient's quality of life (QOL).…”
Section: Discussionsupporting
confidence: 81%
“…Anti‐tumor necrosis factor (TNF) α agents are now well‐known effective treatments that result in both the induction of remission and the maintenance of remission in patients with CD. Several meta‐analyses have reported the efficacy of anti‐TNF therapy for preventing recurrence after surgery; however, the quality of its efficacy reported in some prospective studies differed according to the outcomes, which include clinical recurrence, endoscopic recurrence, and the reoperation rate for recurrent lesions 2–5 . Moreover, adverse events (AEs) associated with anti‐TNF therapy have not been extensively evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…40 Two network meta-analyses suggested that there was no evidence of clinical superiority among anti-TNF agents. 41,42 The influence of obesity on different dose regimens was unknown. To address the influence of obesity on different dose regimens, we did a subgroup analysis of both fixed-dose and weight-based dose anti-TNF agents.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas proctocolectomy is considered curative in UC, clinical and endoscopic postoperative recurrence in CD can happen in the neoterminal ileum in as many as 90% of patients within 12 months of surgical resection and up to 50% of patients can develop a recurrence of symptoms by 5 years. 74 79 Infliximab has been used with good results for prevention of clinical and endoscopic postoperative recurrence in CD. 75 79 …”
Section: Infliximab In Other Specific Ibd Clinical Scenariosmentioning
confidence: 99%